Desafiando a lei da responsabilidade fiscal: um estudo acerca das irregularidades contábeis, financeiras, orçamentárias, operacionais e patrimoniais, fiscalizadas pelo Tribunal de Contas do Estado do Rio Grande do Norte nos anos de 2000 a 2016 - Silva, Maria Helena da Costa (Universidade Federal Rural do Semi-Árido, 2017)
The paper studies the content of accounting, financial, budgetary, operational and patrimonial irregularities audited by the Court of Audit of the State of Rio Grande do Norte in the years 2000 to 2016, aiming to verify the existence of variation in the content and quantity of irregularities raised after Promulgation of the Fiscal Responsibility Law (2000). In the methodology, we manipulate information and data available on the official website of the Court of Audit of the State of Rio Grande do Norte, regarding the judgments of accounts and processes of Municipal Governments, stratifying irregularities and grouping them according to their similarities and temporal evolution. Based on the data collection, there was a variation in the content of irregularities, arising from the new taxes arising from the Fiscal Responsibility Law, whose nonobservance results in irregularities and consequent penalties. We conclude that there has been a reduction in the number of cases related to the irregularities found over the years, which can be attributed to the sense of responsibility stemming from the subjection to the FRL and from the computerized audit practices applied by the supervisory bodies, which inhibit abusive practices by the managers The public
Artigo
Keywords: Lei de responsabilidade fiscal; Teor das irregularidades; Evolução temporal; Law of fiscal responsibility; Content of irregularities; Temporal evolution; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::CIENCIAS CONTABEIS